Determinación de los parámetros físicos, químicos y microbiológicos del agua del canal Latacunga-Salcedo-Ambato en el sector Santa Lucia, periodo 2014 - Illanes Cuasque, Silvia Beatriz (2016)
According to Ex National Water Resources Council ( NWRC ) , nowadays Water National Secretary ( SENAGUA ) , the National Institute of Cotopaxi Irrigation and others show that Cutuchi is a "dead" river by the high levels of pollution. The irrigation canal is 36 kilometers and leads 4 500 liters per second. 17 000 families use it to irrigate 7500 hectares of vegetables and legumes in Tungurahua and Cotopaxi. Every day, 1.8 tons of debris and garbage are dumped into the river.This research was made to determine the extent of contamination found in the canal water irrigation Latacunga -Salcedo - Ambato in the section that crosses Sector Santa Lucia , can say that 6 samples were collected at 2 different points , days and times....